INTELLECTUAL COMPETENCE: ITS PLACE AND IMPORTANCE IN EDUCATION - Abdalova Sayyara Rustamovna (Bright Mind Publishing, 2025)
This article explores the essence of the concept of intellectual potential, its role in the modern educational system, and its significance in shaping the younger generation. The author analyzes methods for developing students' intellectual capabilities within the educational process and addresses existing challenges in this field. Furthermore, the impact of intellectual capital on the socio-economic development of society is substantiated.
Keywords: Intellectual potential, quality of education, human capital, creative thinking, innovative education, cognitive abilities, pedagogical technologies.